(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The achieved education level has a direct influence on incomes and position in thelabour market.It has been also proved that the unemployment level is related to the educationalone(the former decreases as the latter increases). The employment level goes up inrelation to the increase in qualifications obtained at consecutive levels of education. Theabove mentioned thesis have been used to formulate the problem put in this paper. Itconfines itself to finding answers to two important questions: does income and labourmarket position of a person with university qualifications is the basic stimulus for youngpeople to study? What motivated the majority of secondary school leavers to continuetheir education at university level? To verify these two accepted assumptions the authorhas conducted a survey on a random sample of 100 third year students of economics inthe Faculty of Economics and Management of the Technical University of Koszalin; thesurveyed students initiated their study in the academic year 2004/2005.The findings ofthe survey have led to the conclusion that educational decisions of young peopleconcerning further education at an academic level are mainly determined by the desireof self realization or general intellectual development connected with satisfying onesambitions. But in accordance with with the preliminary thesis unimportant proveeconomic determinants: better chances on labour market, higher income, higherstandard of living.